Bond behavior of basalt textile meshes in ultra-high ductility cementitious composites. (1st October 2019) - Jiang, Jiafei; Jiang, Cheng; Li, Benben; Feng, Peng
Abstract: Textile reinforced mortar (TRM) is a composite used in engineering applications of fiber reinforced polymer (FRP) materials. Although TRM can solve the fire resistance and durability issues from epoxy resin, the brittle fracture of traditional mortar greatly influences the bond behavior between the matrix and fibers and subsequently causes a significant decrease in the efficiency of fibers/textiles. A new engineered cementitious composite (ECC), the ultra-high ductility cementitious composite (UHDCC), was recently proposed to replace the mortar in TRM and bond with the textile meshes (termed the TR-UHDCC). This material has the features of multi-microcracking, high strength and ductility under tension. Fundamentally, stress transfer from the textile to the matrix is accomplished through the bond properties, which affect the tensile behaviors of TR-UHDCCs. In this paper, an experimental study on the basalt textile mesh reinforced UHDCC is presented. Double-sided pull-out tests were carried out on 54 specimens. The bond performance was studied by varying the embedded length and mesh geometric properties (mesh spacing and mesh aspect ratio). The restraint of weft yarns was investigated in this study and considered in the bond-slip model for TR-UHDCCs with different textile meshes.